Carotid intima–media thickness relative to cognitive impairment in dialysis patients, and their relationship with brain volume and cerebral small vessel disease. (August 2020) - Zheng, Ke; Qian, Yujun; Lin, Tiaye; Han, Fei; You, Hui; Tao, Xixi; Hou, Bo; Yuan, Jing; Wang, Haiyun; Zhang, Dingding; Lv, Ke; Feng, Feng; et al.
Background: Carotid intima–media thickness (cIMT) is considered a risk factor for and predictor of cerebrovascular disease. In this study, we explored the contribution of cIMT to cognitive impairment (CI) in dialysis patients and the role of cerebral small vascular disease (CSVD) and brain atrophy in this process. Methods: Cognitive function was assessed using a comprehensive cognitive test battery. CSVD and brain volume were assessed by magnetic resonance imaging, and cIMT was measured by ultrasonography. Multivariable analysis and mediation were used to explore the relevant relationships among cIMT, CI, CSVD and brain volume. Results: Seventy-three dialysis patients were enrolled. Approximately 54.8% were diagnosed with increased cIMT. The increased cIMT group was older and had lower serum albumin and creatinine levels than the normal cIMT group. There was no difference in the CSVD prevalence between the different cIMT groups. Patients in the normal, unilaterally and bilaterally increased cIMT subgroups demonstrated a gradual decrease in brain-matter volume and degenerate cognitive function. cIMT was related to cognitive function and gray-/white-matter volume. Increased cIMT was associated with a significantly increased risk of a reduced Mini Mental State Examination/Montreal Cognitive Assessment score and Trail A/B time delay. Mediation analysis showed that CI was mediated by brain-matter volume but not by CSVD. Conclusion: Increased cIMT was an independent risk factor for impairment of global cognitive function, memory, and executive function. The impact of cIMT on cognition was not induced by CSVD but by brain atrophy. cIMT may be a useful tool for screening patients at high risk of CI in the dialysis population.